Islamic Communication: A Critical Realist Perspective - Taqiyuddin, Muhammad (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
In this paper, I explore Islamic communication through a critical realist lens, aiming to enhance the understanding of its principles and applications in contemporary society. The research addresses how critical realism can be utilized to tackle modern challenges in Islamic communication, focusing on three key areas: the conceptualization of Islamic communication within critical realism, the practical implications for contemporary media, and the strategies for addressing intercultural communication challenges. Employing a qualitative methodology that includes theoretical analysis and case studies, I identify significant gaps in the existing literature and propose solutions to bridge these gaps. My findings reveal that integrating critical realism into Islamic communication theory enriches its framework, facilitates the development of practical media applications, and offers valuable strategies for enhancing intercultural communication. This study contributes to a more nuanced understanding of Islamic communication and suggests avenues for future research.